New process for extracting vanadium by direct calcification using the heat of molten vanadium slag - Qu, Jinwei; Zhang, Tingan; Lv, Guozhi; Chen, Yang (Journal of Mining and Metallurgy, Section B: Metallurgy, 2022)
A novel technology for extracting vanadium from molten converter vanadium slag was studied at the laboratory scale by oxidation and calcification. The effect of the cooling method, CaO addition and oxygen blowing time on the phases of calcified vanadium slag was studied. Under the action of oxygen and CaO, vanadium slag will undergo a calcification reaction to form acid-soluble calcium vanadate. The possibility of its main chemical reactions can be calculated by Factsage8.1. The calcified vanadium slag was leached by H2SO4 solution and characterized by XRF, XRD, SEM and EDS techniques. Compared with the traditional process, the new process saved much energy, and it was faster and more efficient. The XRD results showed that CaV2O5, Ca7V4O17 and Ca3V2O8 were gradually formed in the molten vanadium slag with increasing CaO addition. However, when too much CaO was added, Ca2SiO4 and CaTiO3 were also formed. These phases wrapped part of the vanadium and reduced the leaching rate of vanadium. When the mass ratio of Ca to V was 0.75, under the optimal acid leaching conditions (particle size of calcified vanadium slag less than 0.075 mm, leaching temperature 90 ℃, H2SO4 concentration 200 g.L-1, liquid-to-solid ratio 6:1 ml.g-1, leaching time 60 min, stirring speed 300r.min-1), the leaching rate of vanadium from calcified vanadium slag could exceed 90%. The new process not only saved energy and reduced emissions, but also reached the average level of the existing vanadium extraction process.
Keywords: molten vanadium slag; CaO; oxidation; calcification; leaching